The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.prosdent.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polishing procedures and hydrothermal aging on wear characteristics and phase transformation of zirconium dioxide

Abstract: Statement of problem. Yttria-stabilized zirconia used for the fabrication of crowns and fixed\ud \ud prostheses may require intraoral adjustments after placement and cementation. Grinding and\ud \ud polishing methods may result in changes in the surface characteristics of zirconia.\ud \ud Purpose. The purpose of this in vitro study was to assess the effect of polishing procedures on\ud \ud surface roughness, topographical and phase changes of zirconia, and wear of the opposing dentition.\ud \ud Material and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
1
6
0
4
Order By: Relevance
“…used full-contour zirconia crowns for a period of six months [42]; the present study showed similar results when using flat samples for a one-year simulation. In this study, the tested ceramic restorations showed material wear loss that was comparable between the glazed and polished finishes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…used full-contour zirconia crowns for a period of six months [42]; the present study showed similar results when using flat samples for a one-year simulation. In this study, the tested ceramic restorations showed material wear loss that was comparable between the glazed and polished finishes.…”
Section: Discussionsupporting
confidence: 75%
“…Wear has little influence on roughness and no influence on phase transformation [41]; however, glazing and/or polishing ceramic can influence the initial stage of the wear process [15]. Some studies have used polishing procedures applied to zirconia to increase the surface roughness, resulting in phase changes on the zirconia surface [38,42]; conversely, other studies have reported that the polishing surface of zirconia resulted in less wear to the antagonist [43][44][45][46]. Verena et al reported that polished or glazed MZ can provide an alternative to veneered dental restoration [47].…”
Section: Discussionmentioning
confidence: 99%
“…In a standardized temperature glaze method, the underneath ceramic becomes more shrunk when cooled, and compression stress is created at the surface of the glued porcelain. This surface compression stress increases the porcelain strength by preventing the cracks from extending to the porcelain depth, and, by creating a smooth surface in the ceramic, prevents the accumulation of plaque in the ceramic surface (Bartolo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A zircônia pura é um cristal polimórfico que pode ser encontrado em três diferentes formas alotrópicas, dependendo da temperatura: monoclínica (em temperaturas até 1170 ºC), tetragonal (de 1170 até 2370 ºC) e cúbica (2370 ºC até o ponto de fusão) (BARTOLO, D et al, 2017). A adição de estabilizadores como óxidos de ítria e cerium previnem a transformação de fase e mantêm os cristais de zircônia na sua forma mais estável tetragonal em temperatura ambiente (DENRY, I.; KELLY, J. R., Esse fenômeno acontece inicialmente nos grãos mais superficiais, onde água vai se incorporando entre os grãos de zircônia devido ao preenchimento das vacâncias de oxigênio e depois continua para o interior da estrutura do material (CHEVALIER, J.; GREMILLARD, L.;DEVILLE, S., 2007).…”
Section: Inerentes à Zircôniaunclassified
“…A explicação do ocorrido pode estar na possível ocorrência de transformação de fase de tetragonal para monoclínica nos componentes de zircônia dos pilares de G2. Sabe-se que a zircônia pode estar sujeita a essa transformação de fase quando exposta à estresses mecânicos e mudanças de temperatura (HARADA, K. et al, 2016), podendo ser exacerbada na presença de umidade (DENRY, I.; KELLY, J. R, 2008), sendo o fenômeno denominado como degradação em baixa temperatura.Essa transformação de fase ocasiona um aumento de volume nos grãos da zircônia na ordem de 3 a 5%(BARTOLO, D. et al, 2017). Sendo assim, podemos propor que, nas amostras que compõem G2, por terem sido expostas ao dobro de ciclos termomecânicos, o fenômeno da transformação de fase possa ter sido mais expressivo, de modo a compensar a perda de adaptação que houve entre os componentes de titânio e zircônia devido ao desgaste do hexágono do titânio, por meio de um aumento de volume do componente de zircônia.…”
unclassified